Deforestation and Judicial intervention in India - Sharma, Meeta (Integrated Journal for Research in Arts and Humanities, 2023)
Judiciary in India has played a vigorous role in addressing the concern of deforestation in India. Supreme Court’s ruling is an important step in helping to reduce the rate of deforestation in India, and to protect the forests that remain. The concepts of industrialization, urbanization and globalization have negatively prejudiced the natural assets like water, woods, air, etc. Since these resources are essential to human growth, there is an urgent need to protect and use them in a sustainable way. Indeed, forests are a crucial component of our natural ecology. They contribute to preserving ecological equilibrium. They protect the tribal populace, protect gene pools, and shelter wild animals. A successful governance model must strike a balance between development and conservation. Through court rulings, administrative decisions, and legislative measures, India has ensured the preservation of her forests. Though a lot of legislative measures have been made for the maintenance of forests in India, but the input of the judiciary in this regard is beyond compare. Finding means for the Indian government to encourage the preservation of the country's woods is crucial for both the future of the forests and the stability of India. Indian woods may decline as a result of the country's expanding population and associated demands for resources and consumption. Any large decline would result in increasing resource scarcity, which would put more pressure on the government.